Biopolymer nanocomposites : processing, properties, and applications - Dufresne, Alain, 1962-; Thomas, Sabu; Pothan, Laly A (Hoboken, New Jersey : John Wiley and Sons, Inc., 2013)
"The book is an attempt to introduce various biopolymers and bionanocomposites to a student of material sciences. Going beyond mere introduction, the book delves deep into the characteristics of various biopolymers and bionanocomposites and discuses, the nuances of their preparation with a view to help researchers to find out newer and novel applications. Chapter 2 of the book, for instance, describes the preparation of Chitin Nanofibers and their Composites and goes even to the basics like isolation of CNFs from different sources. Chapter 3 is on Chemical Modification of Chitosan and its Biomedical Application. While, Biometric lessons for processing chitin based composites are provided in Chapter 4, the next chapter deals with Morphological and Thermal Investigations of Chitin-based Nanocomposites. Mechanical properties of chitin-based nanocomposites are discussed in Chapter 6 and Preparation and Applications of Chitin Nanofibers/Nanowhiskers is the topic of Chapter 7. Thus, Chapters 2 to 7 are allotted to Chitin and related topics"--
9.3 Chemical Modification of Starch Nanoparticles, Nanomicelles, and Nanocolloids9.4 Role of Chemical Modification in the Application of Starch Nanoparticles; 9.5 Conclusions and Prospects; CHAPTER 10: Starch-Based Bionanocomposite: Processing Techniques; 10.1 Introduction; 10.2 Microstructures of Starch; 10.3 Starch-Based Bionanocomposite; 10.4 Conventional Nanocomposites Manufacturing Techniques; 10.5 Processing Techniques of Starch-Based Bionanocomposites; 10.6 Conclusion; CHAPTER 11: Morphological and Thermal Investigations of Starch-Based Nanocomposites; 11.1 Introduction
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Biopolymers; Nanocomposites (Materials); TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biopolymers; Nanocomposites (Materials); Electronic books; Electronic books